2022
DOI: 10.1063/5.0070079
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals epitaxy growth of 2D ferromagnetic Cr(1+δ)Te2 nanolayers with concentration-tunable magnetic anisotropy

Abstract: Cr(1+δ)Te2 are pseudo-layered compounds consisting of CrTe2 transition metal dichalcogenide (TMD) layers with additional (δ) self-intercalated Cr atoms. The recent search for ferromagnetic 2D materials revived the interest into chromium tellurides. Here, Cr(1+δ)Te2 nanolayers are epitaxially grown on MoS2 (0001), forming prototypical van der Waals heterostructures. Under optimized growth conditions, ultrathin films of only two TMD layers with a single intercalated Cr-layer are achieved, forming a 2D sheet with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…All of those phases exhibit ferromagnetism with a relatively high Curie temperature ( T C ), and CrTe 2 , Cr 3 Te 4 , and CrTe in particular show room-temperature ferromagnetism with T C ≈ 310 K, 320 K, and 340 K, respectively. Such a rather high T C as well as its simple binary composition should be advantageous for 2D spintronics applications, and in fact a growing number of papers have been published in recent years reporting the magnetic properties of this material system down to the ultrathin regime, including the realization of room-temperature ferromagnetism in 2D CrTe 2 , , 2D Cr 3 Te 4 , and 2D CrTe . On the other hand, recent studies on Cr–Te epitaxial thin films grown by molecular-beam epitaxy (MBE) demonstrated a large variation of their magnetic properties depending on the growth condition, ,, implying their sensitive nature to the doping level of the system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All of those phases exhibit ferromagnetism with a relatively high Curie temperature ( T C ), and CrTe 2 , Cr 3 Te 4 , and CrTe in particular show room-temperature ferromagnetism with T C ≈ 310 K, 320 K, and 340 K, respectively. Such a rather high T C as well as its simple binary composition should be advantageous for 2D spintronics applications, and in fact a growing number of papers have been published in recent years reporting the magnetic properties of this material system down to the ultrathin regime, including the realization of room-temperature ferromagnetism in 2D CrTe 2 , , 2D Cr 3 Te 4 , and 2D CrTe . On the other hand, recent studies on Cr–Te epitaxial thin films grown by molecular-beam epitaxy (MBE) demonstrated a large variation of their magnetic properties depending on the growth condition, ,, implying their sensitive nature to the doping level of the system.…”
mentioning
confidence: 99%
“…Such a rather high T C as well as its simple binary composition should be advantageous for 2D spintronics applications, and in fact a growing number of papers have been published in recent years reporting the magnetic properties of this material system down to the ultrathin regime, including the realization of room-temperature ferromagnetism in 2D CrTe 2 , , 2D Cr 3 Te 4 , and 2D CrTe . On the other hand, recent studies on Cr–Te epitaxial thin films grown by molecular-beam epitaxy (MBE) demonstrated a large variation of their magnetic properties depending on the growth condition, ,, implying their sensitive nature to the doping level of the system. Furthermore, a very recent study by angle-resolved photoemission spectroscopy (ARPES) measurements verified the existence of a characteristic semimetallic band region near the Fermi level, demonstrating a unique feature of this material system from a fundamental materials science viewpoint as well.…”
mentioning
confidence: 99%
“…The structure and composition control in the Cr–Te binary system is a known delicate problem. Indeed, a variety of compounds with different stoichiometry can be formed, including CrTe ( T Curie ∼ 200 K), Cr 2 Te 3 ( T Curie ∼ 170 K), Cr 1+1/3 Te 2 ( T Curie ∼ 160–190 K), Cr 3 Te 4 , ( T Curie ∼ 240–320 K), Cr 3 Te 5 , Cr 4 Te 5 (both with a T Curie ∼ 320 K), and Cr 5 Te 8 ( T Curie ∼ 100–220 K). None of these binary alloys are lamellar per se but are thought to consist of CrTe 2 layers where Cr atoms have an octahedral local environment with covalent Cr bridges between these layers.…”
Section: Introductionmentioning
confidence: 99%
“…Structure and composition control in the Cr-Te binary system is a known delicate problem. Indeed a variety of compounds with different stoichiometry can be formed, including CrTe 22 (T Curie ∼200 K), Cr 2 Te 3 [23][24][25] (T Curie ∼170 K), Cr 1+1/3 Te 2 26 (T Curie ∼160-190 K), Cr 3 Te 4 27,28 (T Curie ∼240-320 K), Cr 3 Te 5 , 29 Cr 4 Te 5 30 (both with a T Curie ∼320 K), and Cr 5 Te 8 [31][32][33] (T Curie ∼100-220 K). None of these binary alloys are lamellar per se, but are thought to consist of CrTe 2 layers where Cr atoms have octahedral local environment with covalent Cr bridges between these layers.…”
Section: Introductionmentioning
confidence: 99%